2012
DOI: 10.1093/nar/gks1031
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule kinetics reveal microscopic mechanism by which High-Mobility Group B proteins alter DNA flexibility

Abstract: Eukaryotic High-Mobility Group B (HMGB) proteins alter DNA elasticity while facilitating transcription, replication and DNA repair. We developed a new single-molecule method to probe non-specific DNA interactions for two HMGB homologs: the human HMGB2 box A domain and yeast Nhp6Ap, along with chimeric mutants replacing neutral N-terminal residues of the HMGB2 protein with cationic sequences from Nhp6Ap. Surprisingly, HMGB proteins constrain DNA winding, and this torsional constraint is released over short time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 72 publications
7
92
0
Order By: Relevance
“…Some studies have shown that DNA binding by HMGB1 is dynamic in vitro [30,31] and also in cells [32], while other studies measured slower rates of dissociation [33]. A recent single molecule kinetic study using optical tweezers proposed that microscopic and macroscopic dissociation constants control interactions between HMGB proteins and DNA [34]. The microscopic dissociation events are rapid and involve breaking short range protein-DNA contacts, while the macroscopic events can be measured as slow depending on the experimental conditions, and involve complete dissociation and escape of the protein into solution.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that DNA binding by HMGB1 is dynamic in vitro [30,31] and also in cells [32], while other studies measured slower rates of dissociation [33]. A recent single molecule kinetic study using optical tweezers proposed that microscopic and macroscopic dissociation constants control interactions between HMGB proteins and DNA [34]. The microscopic dissociation events are rapid and involve breaking short range protein-DNA contacts, while the macroscopic events can be measured as slow depending on the experimental conditions, and involve complete dissociation and escape of the protein into solution.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to consider the situation where one has a long dsDNA subject to insertion of kinks when proteins bind to it; this situation has been studied in a variety of single-DNA experiments [50, 51, 52, 53, 54] and is a simplified version of the situation occurring in vivo . A simple polymer model that is useful for considering this situation is a discretized semiflexible chain model, where each segment is a potential binding site for a protein, which when present induces a bend [55]:…”
Section: Dna-protein Interactionsmentioning
confidence: 99%
“…Alternatively, rapidly mixing excess DNA that contain the TF target site can be used to quickly deplete the concentration of unbound TF. However, addition of competitor DNA can bind with partially bound TF states and result in observed dissociation rates that are much higher than the inherent rate of TF dissociation [3033]. …”
Section: Experimental Designmentioning
confidence: 99%